Eculizumab in patients with severe coronavirus disease 2019 (COVID-19) requiring continuous positive airway pressure ventilator support: Retrospective cohort study - Ruggenenti, Piero; Di Marco, Fabiano; Cortinovis, Monica; Lorini, Luca; Sala, Silvia; Novelli, Luca; Raimondi, Federico; Gastoldi, Sara; Galbusera, Miriam; Donadelli, Roberta; Mele, Caterina; Piras, Rossella; et al. (PloS one, 2021)
Complement activation contributes to lung dysfunction in coronavirus disease 2019 (COVID-19). We assessed whether C5 blockade with eculizumab could improve disease outcome. In this single-centre, academic, unblinded study two 900 mg eculizumab doses were added-on standard therapy in ten COVID-19 patients admitted from February 2020 to April 2020 and receiving Continuous-Positive-Airway-Pressure (CPAP) ventilator support from ≤24 hours. We compared their outcomes with those of 65 contemporary similar controls. Primary outcome was respiratory rate at one week of ventilator support. Secondary outcomes included the combined endpoint of mortality and discharge with chronic complications. Baseline characteristics of eculizumab-treated patients and controls were similar. At baseline, sC5b-9 levels, ex vivo C5b-9 and thrombi deposition were increased. Ex vivo tests normalised in eculizumab-treated patients, but not in controls. In eculizumab-treated patients respiratory rate decreased from 26.8±7.3 breaths/min at baseline to 20.3±3.8 and 18.0±4.8 breaths/min at one and two weeks, respectively (p<0.05 for both), but did not change in controls. Between-group changes differed significantly at both time-points (p<0.01). Changes in respiratory rate correlated with concomitant changes in ex vivo C5b-9 deposits at one (rs = 0.706, p = 0.010) and two (rs = 0.751, p = 0.032) weeks. Over a median (IQR) period of 47.0 (14.0-121.0) days, four eculizumab-treated patients died or had chronic complications versus 52 controls [HRCrude (95% CI): 0.26 (0.09-0.72), p = 0.010]. Between-group difference was significant even after adjustment for age, sex and baseline serum creatinine [HRAdjusted (95% CI): 0.30 (0.10-0.84), p = 0.023]. Six patients and 13 controls were discharged without complications [HRCrude (95% CI): 2.88 (1.08-7.70), p = 0.035]. Eculizumab was tolerated well. The main study limitations were the relatively small sample size and the non-randomised design. In patients with severe COVID-19, eculizumab safely improved respiratory dysfunction and decreased the combined endpoint of mortality and discharge with chronic complications. Findings need confirmation in randomised controlled trials.